2016
DOI: 10.1002/ccd.26860
|View full text |Cite
|
Sign up to set email alerts
|

Single‐center experience in percutaneous closure of arterial duct with Amplatzer duct Occluder II additional sizes

Abstract: In our experience, trans-catheter closure of AD of different sizes and morphologies using ADO II-AS is highly feasible, safe and effective also in challenging anatomic/clinical settings. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
(45 reference statements)
1
14
0
Order By: Relevance
“…Four patients experienced events adjudicated by the CEC as a major complication. The implant success rate and closure rate observed in this study are similar to those derived from a literature review (Table 5) involving patient‐level data from 277 patients reported in ten peer reviewed manuscripts 26‐35 from medical centers in Italy, Ireland, United Kingdom, Turkey, Spain, France and Israel, receiving the ADO II AS (95.3% for patients ≤2 kg, 93.2% for patients 2–6 kg, and 100% for patients >2 kg). FDA approval of the Amplatzer Piccolo Occluder was obtained on January 11, 2019.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Four patients experienced events adjudicated by the CEC as a major complication. The implant success rate and closure rate observed in this study are similar to those derived from a literature review (Table 5) involving patient‐level data from 277 patients reported in ten peer reviewed manuscripts 26‐35 from medical centers in Italy, Ireland, United Kingdom, Turkey, Spain, France and Israel, receiving the ADO II AS (95.3% for patients ≤2 kg, 93.2% for patients 2–6 kg, and 100% for patients >2 kg). FDA approval of the Amplatzer Piccolo Occluder was obtained on January 11, 2019.…”
Section: Discussionsupporting
confidence: 81%
“…The relatively small sample size of 50 patients for the IDE was justified on the basis that ADO II AS was a line extension to the first and second generations of Amplatzer Duct Occluders and that the device has been used extensively outside the United States since 2011. Additionally, a body of published clinical experience with the device from outside the United States 26‐35 . provided reasonable assurance that the device had acceptable procedural safety and effectiveness in a real‐world setting, including in infants <2 kg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, 50 years and countless innovations after Porstmann's pioneering work, transcatheter PDA closure remains at the frontier of our field, as illustrated by the concentration of studies related to this topic in the current and recent issues of Catheterization and Cardiovascular Interventions , as well as elsewhere . In this issue, there are four articles focused on transcatheter PDA closure with recently approved, unapproved but dedicated, or off‐label devices, which shine a spotlight on one of the most promising and challenging frontiers in congenital interventional cardiology, percutaneous anatomical intervention in small and preterm infants .…”
mentioning
confidence: 99%
“…Another article in this issue describes a relatively large single‐center experience with PDA closure using the Amplatzer Duct Occluder II Additional Sizes device (ADOII‐AS) , which was developed with an eye toward PDA occlusion in neonates and small infants . Although only a handful of patients in the Mahmoud series could be considered “small,” and none were <3 kg, prior studies with this device have demonstrated successful PDA closure in a number of preterm infants under 2 kg using the ADOII‐AS .…”
mentioning
confidence: 99%